2018
DOI: 10.1038/s41598-018-25048-w
|View full text |Cite|
|
Sign up to set email alerts
|

Toxicity evaluation of Wanzhou watershed of Yangtze Three Gorges Reservoir in the flood season in Caenorhabditis elegans

Abstract: Three Gorges Reservoir (TGR) in the upper stream of Yangtze River in China is a reservoir with the largest and the longest yearly water-level drop. Considering the fact that most of safety assessments of water samples collected from TGR region were based on chemical analysis, we here employed Caenorhabditis elegans to perform in vivo safety assessment of original surface water samples collected from TGR region in the flood season in Wanzhou, Chongqing. Among the examined five original surface water samples, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 72 publications
(62 reference statements)
0
28
0
Order By: Relevance
“…This observation is very different from the effects of surface water samples in the TGR region in the flood season on wild-type nematodes. In wild-type nematodes, it has been shown that acute exposure to the surface water sample collected from the backwater area (W5) in the flood season could cause the significant decrease in locomotion behavior and induction of intestinal ROS production, although exposure to other four surface water samples in the flood season could not cause obvious toxicity 32 . These observations imply that, at least for the site of backwater area, the noticeable difference for the potential effect between surface water in the flood season and surface water in the quiet season may exist on environmental organisms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This observation is very different from the effects of surface water samples in the TGR region in the flood season on wild-type nematodes. In wild-type nematodes, it has been shown that acute exposure to the surface water sample collected from the backwater area (W5) in the flood season could cause the significant decrease in locomotion behavior and induction of intestinal ROS production, although exposure to other four surface water samples in the flood season could not cause obvious toxicity 32 . These observations imply that, at least for the site of backwater area, the noticeable difference for the potential effect between surface water in the flood season and surface water in the quiet season may exist on environmental organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The surface water samples were from 5 sampling sites (W1, shore water; W2, upstream; W3, shore water; W4, downstream; and W5, backwater area) in Wanzhou, Chongqing (Fig. 6), which are the same as those analyzed in our previous study 32 . The sampling season was selected in the quiet season (December 15, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations